The Constitution as an Object of Political Analysis - Vasily K. Belozerov (RUDN Journal of Political Science)
The constitution is typically the primary political and legal act of the state and is a subject of study for representatives of a variety of scientific disciplines. The political science community’s attention to the document remains minimal. Meanwhile, the constitution serves as a valuable source of information. Working with the constitution, one can develop an objective understanding of the state, its origins, current situation, and possibilities for its political course within the country and on the international stage. These circumstances indicate that the constitution is a crucial subject for political science analysis. At the same time, the constitution is an accessible and open document; as a result, there is a risk of its superficial perception due to ignoring several circumstances. This article highlights the fact that numerous interpretations of the term “constitution” have emerged in Russian and international sociopolitical and scientific discourse. There are also alternative state constitutions. The constitution serves to legalize and legitimize the political order, particularly in emergency situations resulting from a change of power. In this regard, it is important to identify essential political clauses of state constitutions. The possibility of discovering evidence of the nation’s identity in the constitution, as well as a solid genetic relationship between the present and the past and future, is critical to comprehending its political relevance. When connecting the principles enshrined in the constitution, it is vital to consider the declarative nature of the document’s provisions as well as their futuristic orientation toward the development of the future. When examining the state constitution, it is essential to consider the broad event, chronological, and other contexts, rather than a simplistic interpretation of its contents.